Fistula formation after excision of extraperitoneal paravaginal teratoma - Ting-Chien Lin; Po-Chuan Chen; Wan-Chen Liu; Chun-Ting Chiang; Yu-Fang Huang (Taiwanese Journal of Obstetrics & Gynecology)
Abstracts: Objective: Mature extragonadal teratomas, particularly at the pelvic extraperitoneal site, are rare. Herein, we report a case of paravaginal teratoma and fistula formation five years post-operation. Case Report: A 23-year-old woman (G4P3A1) presented with a left paravaginal cystic tumor. After transvaginal tumor excision, histopathology revealed a paravaginal dermoid cyst. Five years post-operation, she returned with recurrent symptoms, including fever and perineal pain. Pelvic magnetic resonance imaging showed abscess at the surgical site, with tract-like extensions through the levator ani and vaginal wall. Treatment was administered without surgical intervention. Seven years post-operation, the patient underwent debridement of the left paravaginal abscess via the left perineal route. The patient was diagnosed with an abscess and an epidermal keratinous cyst with a vaginoperineal fistula. No recurrent abscess or fistula formation was encountered four years after debridement and fistulectomy. Conclusion: Preoperative and postoperative counseling should be conducted with long-term follow-up for such patients.